2009
DOI: 10.1080/00016480802294351
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of supraglottic carcinoma: PTEN and thrombospondin 2 are associated with inhibition of lymphatic metastasis

Abstract: Compared with normal laryngeal tissues, the expression of 15.6% (15/96) genes including cathepsin B, cathepsin D, cathepsin L, Ets1, c-Ets2, and PEA3 were up-regulated in both cases of supraglottic carcinoma. Compared with the supraglottic carcinoma with no lymph node metastasis, the expression of metastasis inhibitor genes PTEN and thrombospondin 2 was down-regulated in the supraglottic carcinoma tissue with lymph node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…For miR-335-5p, it was reported that it can suppress invasion of lung cancer cell, neuroblastoma cell and osteosarcoma cells [39][40][41] . In addtion, THBS2 is reported associated with inhibition of supraglottic carcinoma and pancreatic cancer cell invasion 42,43 . These findings partly show the correctness of the our analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…For miR-335-5p, it was reported that it can suppress invasion of lung cancer cell, neuroblastoma cell and osteosarcoma cells [39][40][41] . In addtion, THBS2 is reported associated with inhibition of supraglottic carcinoma and pancreatic cancer cell invasion 42,43 . These findings partly show the correctness of the our analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…The Ets1 transcription factor is normally expressed within the proliferative basal layer of the epidermis (Nagarajan et al, 2009), but in many squamous cell cancers, Ets1 is overexpressed in malignant keratinocytes, where its expression is correlated with invasion and metastasis (Bai et al, 2009;Endo et al, 2006;Keehn et al, 2004;Pande et al, 1999;Saeki et al, 2000;Vairaktaris et al, 2007). In order to address the potential role of Ets1 in keratinocyte biology and in the induction of squamous cell tumors, we generated a mouse model in which we can inducibly express Ets1 in keratinocytes that have already begun their differentiation process.…”
Section: Discussionmentioning
confidence: 99%
“…In normal tissues, Ets1 is expressed only in the basal layer of stratified squamous epithelium (Nagarajan et al, 2009). However, in a large fraction of SCC tumors, Ets1 is highly expressed within the malignant keratinocytes, and its levels directly correlate with the invasive and metastatic potential of the tumor (Bai et al, 2009;Endo et al, 2006;Keehn et al, 2004;Pande et al, 1999;Saeki et al, 2000;Vairaktaris et al, 2007). Tumors that express high levels of Ets1 typically also express high levels of several matrix metalloprotease (Mmp) genes (Dittmer, 2003;Hahne et al, 2008;Lincoln and Bove, 2005) and Ets1 has been shown to directly regulate expression of multiple Mmp genes (Baillat et al, 2006;Nagarajan et al, 2009;Ozaki et al, 2000;Reisdorff et al, 2002;Wei et al, 2009;Westermarck et al, 1997).…”
Section: Ets1 Blocks Terminal Differentiation Of Keratinocytes and Inmentioning
confidence: 99%
“…THBS2 suppresses angiogenesis by inhibiting endothelial cell migration, inducing endothelial cell apoptosis and preventing the interaction of growth factors with the cell surface receptors of the endothelial cell . In supraglottic cancer, THBS2 gene expression seems inversely correlated with nodal metastases …”
Section: Introductionmentioning
confidence: 99%
“…9 In supraglottic cancer, THBS2 gene expression seems inversely correlated with nodal metastases. 10 TACSDT2, also known as TROP-2, belongs to a unique family of transmembrane glycoproteins that has a regulatory role in cell-cell adhesion and has a key controlling role in human cancer growth. Tumor development is quantitatively driven by TACSTD2 expression levels in many tumors.…”
Section: Introductionmentioning
confidence: 99%